Recolhimento de medicamentos no mercado brasileiro (2016-2020) - Pozzer, Mariana (My University, 2020)
This study aimed to analyze the drug recall scenario in the brazilian market from january 2016 to june 2020. The data were collected from ANVISA website, data on the drug, commercial name, therapeutic class, pharmaceutical form, dose / concentration, quantity of lots, company holding the registration, manufacturer company, recall communicated by ANVISA or company, the reason for recall, resolution number (RE), date, sale with or without medical prescription and regulatory category. After RE analysis, 414 recall was detected. The reasons found were quality deviation (n = 255), failure in fiscal analysis (n = 56), non-compliance with Good Manufacturing Practices (GMP) (n = 54), non-compliance with registration (n = 31) and failure in a stability study (n = 18). The therapeutic class that most recalled was anti-ulcer agents (n = 63), followed by antimicrobials (n = 52) and anti-hypertensive (n = 52). There were many recalls related to active pharmaceutical ingredients (n = 105), 84 of which (80%) due to nitrosamine impurity. Drugs with quality outside the specification were also frequent, being detected in fiscal analysis, in a stability study, in quality control and even by the receiving establishments. The lack of adequacy to GMP was probably where there was the greatest number of lots recall, which wasn't possible to estimate, as in these cases there is the recall of all valid lots and the suspension of manufacture, import, distribution, marketing and use of them, as long as there is no adaptation to GMP by the manufacturer. [resumo fornecido pelo autor]
Este estudo teve como objetivo analisar o cenário de recolhimento de medicamentos do mercado brasileiro no período de janeiro de 2016 a junho de 2020. Por meio do site da ANVISA obteve-se dados do fármaco, nome comercial, classe terapêutica, forma farmacêutica, dose / concentração, quantidade de lotes, empresa detentora do registro, empresa fabricante, recolhimento comunicado pela ANVISA ou empresa, qual foi o motivo do recolhimento, número da resolução (RE), data, venda com ou sem prescrição médica e categoria regulatória. Após análise das RE detectou-se 414 casos de recolhimento. Os motivos encontrados foram desvio de qualidade (n=255), reprovação em análise fiscal (n=56), não conformidade com as Boas Práticas de Fabricação (BPF) (n=54), não conformidade com registro (n=31) e reprovação em estudo de estabilidade (n=18). A classe terapêutica que mais teve recolhimentos foi a dos antiulcerosos (n=63), seguida pelos antimicrobianos (n=52) e anti-hipertensivos (n=52). Houveram muitos recolhimentos relacionados aos insumos farmacêuticos ativos (n=105) sendo 84 destes (80%) por impureza nitrosamina. Medicamentos com qualidade fora da especificação também foram frequentes, sendo detectados nas análises fiscais, em estudo de estabilidade, no controle de qualidade e até mesmo pelos estabelecimentos receptores. A não adequação às BPF provavelmente foi onde houve o maior número de lotes recolhidos, o qual não foi possível estimar, pois nestes casos há o recolhimento de todos os lotes válidos e a suspensão da fabricação, importação, distribuição, comercialização e uso dos mesmos, enquanto não houver adequação às BPF pela empresa fabricante. [resumo fornecido pelo autor]
Keywords: Farmácia; Medicamentos; Vigilância sanitária; Indústria farmacêutica - Brasil; Agência Nacional de Vigilância Sanitária (Brasil)